Magnetic Resonance Imaging Evaluation of Patellar Tendon Graft Remodelling after Anterior Cruciate Ligament Reconstruction with or without Platelet-Rich Plasma. (April 2013) - Seijas, Roberto; Ares, Oscar; Catala, Jordi; Alvarez-Diaz, Pedro; Cusco, Xavier; Cugat, Ramon
Purpose: To evaluate the stages of patellar tendon graft remodelling using magnetic resonance imaging (MRI) after anterior cruciate ligament (ACL) reconstruction with or without platelet-rich plasma (PRP) injection. Methods: 98 patients aged 18 to 65 years with complete rupture of the ACL were randomised to undergo reconstruction with the autologous patellar tendon grafts with or without PRP injection. For the PRP group, 8 ml of PRP was obtained in the surgery room and was percutaneously injected into the suprapatellar joint after portal suture. MRI was obtained at months 4, 6, and 12. Remodelling stages of the grafts were classified as hypointense, mildly hyperintense, moderately hyperintense, severely hyperintense, and diffusely hyperintense by a radiologist blinded to treatment allocation. Results: More patients in the PRP group than controls attained higher stages of remodelling at month 4 (p=0.003), month 6 (p=0.0001), and month 12 (p=0.354). Conclusion: PRP enabled faster remodelling of patellar tendon grafts.